A new modification of LEACH for efficient energy in WSN - Taous Lechani; Victor Tourtchine; Said Amari (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The limited energy of nodes in wireless sensor networks and the impossibility of replacing their batteries, have lead to protocols development which optimize and balance the energy consumption over the network. LEACH is the most used hierarchical protocol. However, one major weakness of the LEACH protocol lies in both of its random cluster formation and cluster head election. In this paper, we present two new protocols based virtual grid clustering on coverage area. In the first one, sensing area is devided into grids as squares named as VSG-LEACH and in the second one into grids as hexagons named as VHG-LEACH. In each zone, one cluster head is elected according to its residual energy and its distance from the cell center. The simulation results show that the network lifetime is prolonged by 169.67% and the energy consumption is improved by 80.97% compared to LEACH protocol.